Clinical and biochemical profile of patients with viral hepatitis at tertiary care centre - Birajdar, Sidheshwar Virbhadraappa; Chavan, Sheshrao Sakharam; Mundhe, Sanjay A.; Bhosale, Manisha G. (International Journal of Advances in Medicine, 2017)
Background: Viral hepatitis is known since ancient times. Hepatitis is an inflammation of the liver, most commonly caused by a viral infection. Different species of viruses, including Cytomegalovirus, Epstein-Barr, Herpes simplex, Adenovirus, Coxsackie virus and others cause parenchymal hepatic inflammation, but the term viral hepatitis generally implies to the five hepatotropic viruses: Hepatitis A, B, C, D and E virus. Methods: This observational study was done from August 2014 to November 2016 in department of medicine of a medical college using a structured questionnaire. Results: Anorexia was the most common symptom; followed by fatigue; nausea and vomiting. Total serum bilirubin and direct serum bilirubin were raised in all cases of hepatitis A and E. Raised SGPT and SGOT were observed in all cases of Hepatitis A and E. Among 43 patients of hepatitis B, SGPT and SGOT were raised in 32 and 31 cases respectively. Raised alkaline phosphatase was observed in 27; 25 and 16 cases of hepatitis A; B and E respectively. Raised prothrombin time was observed in 12; 11; 01and 09 of Hepatitis A; B; C and E cases respectively. Conclusions: Viral hepatitis is an important heath care problem in India as it occurs epidemically and sporadically. The variability in nature of the disease regarding its onset, presenting symptoms, clinical course and development of complications are important aspects. So, it is very essential for health care professionals to be aware of all aspects of it so that it is detected and treated early.